Three-dimensional reduced graphene oxide powder for efficient microwave absorption in the S-band (2–4 GHz). Issue 41 (12th May 2017) - Fang, Shuai; Huang, Daqing; Lv, Ruitao; Bai, Yu; Huang, Zheng-Hong; Gu, Jialin; Kang, Feiyu
Abstract : Three-dimensional reduced graphene oxide (3D-rGO) powders are synthesized and demonstrate remarkably enhanced microwave absorption in the S-band (2–4 GHz). Abstract : Efficient absorption in the S-band (2–4 GHz) has been a very challenging task for developing high-performance microwave absorption materials. Three-dimensional reduced graphene oxide (3D-rGO) powders were prepared by using a hydrothermal method and subsequent thermal treatment. It is found that as-prepared 3D-rGO could significantly enhance the electromagnetic wave attenuation in 2–4 GHz. When the content in the paraffin matrix is 4%, the 3D-rGO shows the strongest absorption in S-band, and the absorption will get stronger with the increase of coating thickness. When the thickness is 5 mm, the bandwidth of reflection loss less than −5 dB is in the range of 2.3 to 4.1 GHz, that is, it can almost cover the whole S-band. The excellent microwave absorption could be attributed to the honeycomb-like structures and the strong polarization of 3D-rGO powders. Considering the low density and good corrosion resistance, 3D-rGO powders may serve as an excellent component for the design of lightweight electromagnetic wave absorption coatings.